Analysis of trends and hotspots in the research on sleep disorders of maintenance hemodialysis patients based on bibliometrics - Li Huang; Siyu Li; Jing Zeng (Frontiers in Psychiatry, 2025)
ObjectiveTo explore the research hotspots and frontiers of sleep disorders in patients undergoing maintenance hemodialysis (MHD) over the past 15 years.MethodsRelevant literature published from January 1, 2010, to April 1, 2025, was retrieved from the Web of Science Core Collection database. Bibliometric analysis and VOSviewer software were employed to visualize data on countries, institutions, journals, authors, and keywords.ResultsA total of 337 articles were included. The annual publication volume demonstrated an upward trend. China ranked first in contributions (21.3%), followed by the United States (16.9%) and Turkey (12.8%). BMC Nephrology was the most active journal, and the University of Pittsburgh emerged as the leading institution. One major author collaboration group was identified. Research hotspots focused on specific sleep disorders (e.g., sleep apnea, restless legs syndrome), clinical outcomes (e.g., mortality, prevalence), influencing factors, quality of life, and interventions. Emerging trends included psychological and physical comorbidities such as depression, anxiety, pain, and fatigue.ConclusionBibliometric analysis combined with visualization tools effectively maps the current landscape and frontiers of sleep disorder research in MHD patients. These findings provide evidence-based references for future nursing practices and interdisciplinary studies in this field.